Evaluasi Kerentanan Fisik dan Potensi Pengembangan Jembatan Titi Gantung sebagai Cagar Budaya Kota Medan - Radwa, Sahirah; Mahmuda, Aqidatul; Fitriandini, Windi; Syalsabila, Nadya; Nuraini, Cut (Jurnal Teknik dan Teknologi Indonesia, 2024)
Titi Gantung is a colonial-era pedestrian overpass built in 1885 in Medan, North Sumatra, that has been designated a municipal cultural heritage structure. As a historic bridge that still functions daily amid rapid urban change, it faces mounting physical pressure from age, weather exposure, and inadequate drainage, while also holding considerable potential as an urban heritage tourism asset. This study aims to evaluate the physical vulnerability and development potential of Titi Gantung using a qualitative Strengths-Weaknesses-Opportunities-Threats (SWOT) approach. Data were collected through field observation, photographic documentation, a literature review, and a questionnaire distributed to 31 respondents using a five-point Likert scale. The results show that the bridge's principal strengths lie in its historical identity and strategic location, its main weaknesses relate to limited supporting facilities and cleanliness, its opportunities lie in heritage-tourism development and social-media promotion, and its foremost threats are inadequate maintenance, vandalism, and uncontrolled functional change. These findings indicate that Titi Gantung requires an integrated conservation and community-based management strategy to sustain its historical value.